The effect of teaching methods on student’s achievement in writing recount text at SMP Negeri 4 Tanjung Balai - Harahap, Nurul Husnah; Sinaga, Dwi Pebrina; Tampubolon, Marlina (Institute of Computer Science (IOCS), 2024)
This study was focused on the investigation of the effect of using teaching methods on students’ Achievement in Writing Recount text. This study discovered the effect of using cooperative Integrated Reading and composition (CIRC) method on Student’ Writng Achievement. It was conducted by using students of SMP Negeri 4 Tanjungbalai divided into two groups, namely experimental and control group. The experimental group was taught by using CIRC method, while the control group was taught by using lecture method. The instrument of collecting data was writing recount test. The data were analyzed by using t-test formula. It was also obtained that tobserved is higher ttable (2.603>1.673) at the level of significance (? = 0,05) and degree of freedom (df) = 58. It means that null hypothesis was successfully rejected and alternative hypothesis was accepted. The result of this study showed that teaching writing by using CIRC method was higher than by using lecturing method. It method is appropriate to be applied for writing.